Reviving Heritage: Conservation and Infill Design at Alimar Hotel Malang - Kenny David Ariyanto; Anthony Srestha Rares; Rayden Lauwirya Soegiarto; Timoticin Kwanda (Advances in Civil Engineering and Sustainable Architecture, 2025)
Colonial buildings in cities like Malang face pressure to modernize without losing historical identity. This study applies a descriptive qualitative method involving field observations, literature review, and interviews, analyzed using conservation architecture principles. The research highlights the importance of preserving colonial heritage by adapting it to modern functions while maintaining architectural integrity. The transformation involved converting residential spaces into hotel facilities and adding new infill structures to support the new function. Findings reveal that interventions respecting minimal intervention, reversibility, and adaptive reuse enable both preservation of heritage and modern functionality This research aims to promote sustainable preservation practices and demonstrates how adaptive reuse can help colonial buildings remain functional and relevant in today’s urban context.